Low Temperature Synthesis of Large‐Size Anatase TiO2 Nanosheets with Enhanced Photocatalytic Activities. Issue 48 (10th November 2017) - Tang, Xiao; Chu, Wanyi; Qian, Jueshi; Lin, Jingcheng; Cao, Guozhong
Abstract: TiO2 nanosheets have continuously been intriguing due to their high surface activities as photocatalyst but still challenging to synthesis large‐scale 2D nanostructures. A special microstructure evolution of TiO2, ripening in aqueous solution at low temperature (≈4 °C), is found for the first time, i.e., from the initial aperiodic atom‐networks gradually into low crystallized continuous spongy structure with small crystal facets and ultimately forming large‐size anatase nanosheets with exposed (101) and (200) facets. Based on this finding, the synthesized anatase TiO2 nanosheets possess monodispersed large‐scale 2D nanostructure so as to exhibit appreciable quantum size effects and remarkable enhanced optical absorption capacity. Using photocatalytic reduction of Cr (VI) to Cr (III) as the probe reaction to evaluate photocatalytic activities of the TiO2 nanosheets, the reductivity of Cr (VI) achieves 99.8% in 15 min under irradiation of 200–800 nm light. At the same time, an in situ Cr (III)‐doping occurs spontaneously and triggers pronounced visible light driven photocatalysis, reducing 99% of Cr (VI) in 100 min under irradiation of 400–800 nm light. Abstract : The special microstructure evolution of TiO2 is found, from the initial aperiodic 2D atom‐networks gradually growing into ultrathin anatase TiO2 nanosheets, when aged in aqueous solution at the low temperature of ≈4 °C. Under irradiation of natural sunlight, the monodisperse TiO2 nanosheets exhibit high photocatalytic activity to reduce Cr (VI) to Cr (III) owing to high optical absorption capacity and low‐temperature‐doping effects.